Characterization and comparison of gut microbiota in patients with acute pancreatitis by metagenomics and culturomics - Liang Gong; Xue Li; Li Ji; Guorong Chen; Ziying Han; Lei Su; Dong Wu (Heliyon)
Acute pancreatitis (AP) is a common gastrointestinal disorder with a high mortality rate. This study sought to identify the microbial community structure in patients with AP using metagenomics and culturomics. Compared to healthy controls, patients with AP exhibited a significant decrease in alpha diversity; a higher abundance of unclassified Enterococcus species (sp), Enterococcus faecium, and Enterococcus faecalis; and a lower abundance of Eubacterium rectale. A total of 336 isolates from 25 genera and 44 species were obtained by sample cultivation. The dominant species identified in patients with AP were Enterococcus faecium and Klebsiella grimontii, whereas those in the healthy controls were Enterococcus faecium, Escherichia coli, and Bacteroides faecis. Our research has contributed to the expanded understanding of the genome, diversity, and function of the intestinal microbiota in patients with AP and provided some reference for selecting culture medium and sample processing methods.